The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12936-021-03679-1
|View full text |Cite
|
Sign up to set email alerts
|

Community acceptance of reactive focal mass drug administration and reactive focal vector control using indoor residual spraying, a mixed‐methods study in Zambezi region, Namibia

Abstract: Background In Namibia, as in many malaria elimination settings, reactive case detection (RACD), or malaria testing and treatment around index cases, is a standard intervention. Reactive focal mass drug administration (rfMDA), or treatment without testing, and reactive focal vector control (RAVC) in the form of indoor residual spraying, are alternative or adjunctive interventions, but there are limited data regarding their community acceptability. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A few studies have reported IRS acceptance to be generally high, including an investigation in Tanzania [58] where about 95% of participants reported agreeing to receiving IRS, primarily because they recognized that mosquitoes transmitted the malaria parasite and the spray reduced mosquito abundance. Another qualitative study in Namibia that evaluated people's acceptance of case-reactive IRS of households [16], virtually all participants accepted the IRS, in part because they perceived the importance of malaria risk, would receive free healthcare with the IRS, and were educated by respectful study team members. Most studies, however, reported extensive reluctance and strong resistance to household IRS, including reports from Ghana [59], Iran [60], and Mozambique [61], for example.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported IRS acceptance to be generally high, including an investigation in Tanzania [58] where about 95% of participants reported agreeing to receiving IRS, primarily because they recognized that mosquitoes transmitted the malaria parasite and the spray reduced mosquito abundance. Another qualitative study in Namibia that evaluated people's acceptance of case-reactive IRS of households [16], virtually all participants accepted the IRS, in part because they perceived the importance of malaria risk, would receive free healthcare with the IRS, and were educated by respectful study team members. Most studies, however, reported extensive reluctance and strong resistance to household IRS, including reports from Ghana [59], Iran [60], and Mozambique [61], for example.…”
Section: Discussionmentioning
confidence: 99%
“…Community acceptance of RACDT was generally high, 39 42 with refusal rates of 2% or lower. In Namibia, some “hesitation/resistance” during pretrial interviews was reported, but community engagement and sensitization improved participation ( Supplemental Table 9 ).…”
Section: Resultsmentioning
confidence: 98%
“…In Namibia, some “hesitation/resistance” during pretrial interviews was reported, but community engagement and sensitization improved participation ( Supplemental Table 9 ). 42 Similarly in Senegal, high RACDT participation was attributed to advanced cascade sensitization, making follow-up appointments for absent members, and conducting return visits to the compound the same or next day. 40 Lack of community confidence in community health workers’ (CHWs’) ability to address diseases other than malaria and community unwillingness to visit CHWs for malaria testing were reported from Zambia.…”
Section: Resultsmentioning
confidence: 99%
“…Focal snail control has been implemented successfully in other settings, such as Egypt and Mali [ 26 , 27 ]. In similar low-prevalence settings for malaria, focal MDA plus vector control have been applied to reduce transmission [ 28 , 29 ] and reactive case detection, and focal MDA against malaria were shown to have a high community acceptance in Namibia [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%